Simplifying The World’s Best Fairy Tales for Teaching Narrative Texts in Junior High School - Pindha Kaptiningrum (Cakrawala: Jurnal Pendidikan, 2016)
The World’s Best Fairy Tales is a well-known book and contains sixty nine best-loved stories over the world. However, the storieswritten in The World’s Best Fairy Tales contain too long and complicated sentences for Junior High School students in Indonesiaespecially in SMPN 1 Slawi. This problem can be solved by simplifying of The World’s Best Fairy Tales. The R&D steps are used toknow the existing materials, kinds of materials needed by the students, how the simplified materials developed, the advantages ofteaching and learning using the simplified materials, and the effectivennes of the simplified materials toward students’ achievement.The result was simplified materials giving positive influence to the students and able to motivate them in learning English.